Building Student Abilities: Making Reports And Demonstrations Through Project-Based Learning - Hanifah Hanifah (Jurnal Pendidikan Matematika Raflesia, 2021)
The Project-Based Learning (PjBL) Model was used to carry out Primary Level Mathematics Capita Selecta Learning. PjBL was used in seven steps: 1) Discussing the syllabus, materials, groups, math problem, math props, and report form; 2) Collecting data, write reports, and create math props; 3) Presentation; 4) Revising the report in light of the discussion's findings; 5) Reports are being uploaded in revised form; 6) Each group assesses the report of the other group; 7) Implementing Posttest. The purpose of this study was to determine students' creativity and teaching ability in PjBL in the Subject Primary Level Capita Selecta Learning in 2019/2020. The subjects were class B of the fourth semester of Mathematics Education FKIP UNIB2019/2020, with a total of 28 students. This research was conducted ex-post facto, which means that it examined events that had already occurred and then traced back to determine the factors that caused these events. The instrument used to collect information about student creativity was developed as a result of group evaluations of previous group reports. Post-test results are used to calculate the value of learning ability. The results were obtained after the data was processed: The average report score for each group was 83.88, the post-test average score was 85.85, and both were categorized as very good.